Associations between contextual factors and school engagement: a longitudinal study of profiles - Saracostti, Mahia; de Toro, Ximena; Miranda, Horacio; Miranda-Zapara, Edgardo; Lara, Laura; Hernández, María Teresa (Frontiers in Education, 2024)
School engagement, encompassing affective, behavioural, and cognitive dimensions, is key to promoting school retention and preventing absenteeism. Previous research has shown that maintaining high engagement is crucial for a positive educational trajectory. This study investigates the individual contributions of contextual factors, including family, teacher, and peer support, on students who initially had a low level of school engagement in one dimension and then advanced to a higher level in the same dimension over time. The study involved students enrolled in their first year of secondary education in public schools in Chile during 2021, with the same students being evaluated again the following year. We used means cluster analysis to identify a group of students who initially had low school engagement but showed high engagement by the second evaluation. This allowed us to identify profiles of school engagement longitudinally. Our results indicated that contextual factors had a stronger association with affective engagement, followed by cognitive and behavioral engagement, respectively. Among the contextual factors, family and teachers had a stronger impact compared to peers. These findings highlight the importance of adults, particularly family and teachers, in enhancing school engagement during secondary education.